2017
DOI: 10.3928/01477447-20161017-04
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Hypothermia in Total Hip and Knee Arthroplasty

Abstract: Total hip arthroplasty (THA) and total knee arthroplasty (TKA) are common and successful orthopedic procedures, and as their frequency continues to increase substantially, the focus on limiting perioperative complications heightens. Intraoperative normothermia is recommended to minimize additional complications, but limited evidence exists regarding the effect of hypothermia on orthopedic patients. The purpose of this retrospective study was to determine the incidence of perioperative hypothermia in the settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 36 publications
5
35
1
1
Order By: Relevance
“…Perioperative hypothermia commonly is defined as a body temperature less than or equal to 36.0° C (≤96.8° F) during the perioperative continuum of care . Multiple studies describe negative outcomes associated with inadvertent hypothermia, including surgical site infection, coagulation dysfunction, increased intraoperative blood loss, sepsis, and mortality . Although the seriousness of postoperative complications varies, one research group found that mortality increased fourfold in patients who had experienced perioperative hypothermia .…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Perioperative hypothermia commonly is defined as a body temperature less than or equal to 36.0° C (≤96.8° F) during the perioperative continuum of care . Multiple studies describe negative outcomes associated with inadvertent hypothermia, including surgical site infection, coagulation dysfunction, increased intraoperative blood loss, sepsis, and mortality . Although the seriousness of postoperative complications varies, one research group found that mortality increased fourfold in patients who had experienced perioperative hypothermia .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The higher incidence of perioperative hypothermia may be related to decreased thermoregulation in older adults . Some studies have shown a significantly higher incidence of perioperative hypothermia in female patients; others show a higher incidence in male patients …”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some studies showed the contrary result. Even though hypothermia increases the amount of estimated blood loss, it did not increase transfusion rate, postoperative complications, length of hospital stay or the rate of 30-day readmission [34]. In general, it is still recommended that patients' core temperature should be constantly monitored throughout the operation to maintain normothermia status.…”
Section: Maintenance Of Normothermiamentioning
confidence: 99%